PUTUSAN MAHKAMAH AGUNG NOMOR. 37/P/HUM/2017 (Ditinjau Dari Asas Keadilan) - Ikhsan Helmi Lubis (Institut agama islam negeri Padangsidimpuan, 2021)
In Decision Number 37 P / HUM / 2017 concerning the Implementation of Transportation of People with Public Motorized Vehicles Not on Route, the Supreme Court revoked all of the Petitioners' petitions by stating PM. Number 26 of 2017 contradicts Law Number 20 of 2008. As a result of this decision, it raises pros and cons among the public. One party stated that this decision was a decision that was responsive to innovation in the transportation sector. On the other hand, stated that the legal considerations used by the Supreme Court were inadequate because they did not use Law Number 22 of 2009 and Government Regulation Number 74 of 2014 which were the basis for making PM Number 26 of 2017 and this decision did not reflect justice for the parties. The method used to solve the problem in this study is to use a type of library research with a normative juridical approach while the type of research used is descriptive analytical. Based on these problem, the authors will analyze The Supreme Court’s decision from the principle of justice. Based on the results of research using the principle of justice, The Supreme Court Decision Number 37/P/HUM/2017 tended to side with the Petitioners by revoking all the provisions petitioned for judicial review. Even though this provision is an ideal provision to be maintained in order to create balance, equality and non-discrimination between Special Charter Transportation and Conventional Taxis.